2024
DOI: 10.1002/jmrs.756
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of brain metastases from lung cancer using magnetic resonance neuroimaging: Clinical and technical aspects

Sadegh Ghaderi,
Sana Mohammadi,
Mahdi Mohammadi
et al.

Abstract: IntroductionBrain metastases (BMs) are common in lung cancer (LC) and are associated with poor prognosis. Magnetic resonance imaging (MRI) plays a vital role in the detection, diagnosis and management of BMs. This review summarises recent advances in MRI techniques for BMs from LC.MethodsThis systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. A comprehensive literature search was conducted in three electronic databases: PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 93 publications
0
0
0
Order By: Relevance
“…We are writing to emphasize the clinical implications of using ultra-high field (UHF) magnetic resonance imaging (MRI) (7 Tesla (7T) MRI) for the detection and management of systemic malignant tumors such as brain metastases (BMs). Our two recent systematic reviews, based on 89 studies of BMs from breast and lung cancers, have indicated the critical role of conventional and advanced MRI in diagnosing and monitoring BMs [1,2].…”
mentioning
confidence: 99%
“…We are writing to emphasize the clinical implications of using ultra-high field (UHF) magnetic resonance imaging (MRI) (7 Tesla (7T) MRI) for the detection and management of systemic malignant tumors such as brain metastases (BMs). Our two recent systematic reviews, based on 89 studies of BMs from breast and lung cancers, have indicated the critical role of conventional and advanced MRI in diagnosing and monitoring BMs [1,2].…”
mentioning
confidence: 99%